2018
DOI: 10.1007/978-3-030-04414-5_31
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Symmetries in Drawings of Graphs

Abstract: Symmetry is an important factor in human perception in general, as well as in the visualization of graphs in particular. There are three main types of symmetry: reflective, translational, and rotational. We report the results of a human subjects experiment to determine what types of symmetries are more salient in drawings of graphs. We found statistically significant evidence that vertical reflective symmetry is the most dominant (when selecting among vertical reflective, horizontal reflective, and translation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Symmetry perception in graphs was also investigated by de Luca et al [127]. An online study using data from 56 participants found that horizontal symmetry was considered most important, followed by vertical and then translational symmetry.…”
Section: A: Graph Classes and Topologymentioning
confidence: 98%
See 1 more Smart Citation
“…Symmetry perception in graphs was also investigated by de Luca et al [127]. An online study using data from 56 participants found that horizontal symmetry was considered most important, followed by vertical and then translational symmetry.…”
Section: A: Graph Classes and Topologymentioning
confidence: 98%
“…Summary: There seems to be a tendency to hierarchical drawings in a top-to-bottom style with straight links [123], [124], also identifying a geodesic-path behavior by using eye tracking, for example, to explore search and information processing tasks [125]. Symmetry is an important feature [126], [127] as well as outlines [128] and similarity [131]. For meta-properties, it seems that a multi-dimensional scaling layout was best [129].…”
Section: A: Graph Classes and Topologymentioning
confidence: 99%
“…In order to distinguish inputs of different sizes, we refer to layouts in our dataset as small or large based on the number of vertices, |V |. A small layout has |V | ∈ [5,8] -SmallSym: small reflective symmetric layout -SmallNonSym: non symmetric generated from SmallSym with random node positions -ReflectionalLarge: large reflective symmetric layouts with random axis of symmetry -NonSymLarge: non symmetric generated from ReflectionalLarge layouts -HorizontalLarge: large reflective symmetric layouts with a 0 degree axis of symmetry -VerticalLarge: large reflective symmetric layouts with a 90 degree axis of symmetry -RotationalLarge: rotational symmetric with random axes between 4 and 10 -TranslationalLarge: translational symmetric translated along x-axis…”
Section: Datasetsmentioning
confidence: 99%
“…We used the procedure for generating a graph and a reflectional symmetric layout with the "parallel lines" feature following the algotithm in [8] as follows. Given a graph with n 2 vertices, called a component, we assign to each vertex of the component positive random coordinates.…”
Section: Reflectional Layout Generationmentioning
confidence: 99%
See 1 more Smart Citation